2016
DOI: 10.1097/rlu.0000000000001313
|View full text |Cite
|
Sign up to set email alerts
|

68Ga DOTATATE PET/CT of Non–FDG-Avid Pulmonary Metastatic Hemangiopericytoma

Abstract: We present the FDG and Ga DOTATATE PET/CT findings of a 68-year-old woman with pulmonary metastases 28 years after her initial diagnosis of central nervous system hemangiopericytoma. The largest of the pulmonary lesions showed prominent Ga DOTATATE uptake with comparatively minimal FDG avidity. Hemangiopericytoma is a rare mesenchymal tumor that arises from malignant pericytes, cells that form the walls of capillaries and postcapillary venules. This case demonstrates the potential of radiolabeled somatostatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Somatostatin receptor expression has been identified in pericytes from patients with interstitial lung disease 16 and retinal disease, 17 and avid 68 Ga-DOTATATE uptake has also been reported in a patient with a rare metastatic hemangiopericytoma. 18 Although endothelial cell SSTR2 expression has also been reported, 19 data from large publicly available RNAseq databases show very low or no SSTR2 expression in endothelial cells (eg, European Blueprint Study, 20 Tabula sapiens human cell atlas 21 ), which is consistent with our findings. SSTR2 expression in adipose tissue is corroborated by data from the Human Protein Atlas.…”
Section: Discussionsupporting
confidence: 89%
“…Somatostatin receptor expression has been identified in pericytes from patients with interstitial lung disease 16 and retinal disease, 17 and avid 68 Ga-DOTATATE uptake has also been reported in a patient with a rare metastatic hemangiopericytoma. 18 Although endothelial cell SSTR2 expression has also been reported, 19 data from large publicly available RNAseq databases show very low or no SSTR2 expression in endothelial cells (eg, European Blueprint Study, 20 Tabula sapiens human cell atlas 21 ), which is consistent with our findings. SSTR2 expression in adipose tissue is corroborated by data from the Human Protein Atlas.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, 68 Ga -Dodecane tetra-acetic acid tyrosine-3-octreotate ( 68 Ga-DOTATATE) is a PET radiopharmaceutical usually used for neuroendocrine-tumor imaging and now increasingly considered as an adjunctive imaging tracer for multiple solid neoplasms, including mesenchymal tumors [ 39 ]. Similarly to 111 In-Pentetreotide, 68 Ga-DOTATATE is a positron-emitter radiolabeled somatostatin analogue able to reveal a high concentration of surface SSRs, with the advantages of superior spatial resolution and accuracy, faster acquisition and lower radiation exposure [ 24 ]. In particular, Hung et al found negligible FDG uptake but intense 68 Ga-DOTATATE avidity of pulmonary metastases in a 68-year-old woman affected by primitive intracranial HPC [ 24 ].…”
Section: Evidence-based Medicine Of Pet/ct In Intracranial Solitary F...mentioning
confidence: 99%
“…Similarly to 111 In-Pentetreotide, 68 Ga-DOTATATE is a positron-emitter radiolabeled somatostatin analogue able to reveal a high concentration of surface SSRs, with the advantages of superior spatial resolution and accuracy, faster acquisition and lower radiation exposure [ 24 ]. In particular, Hung et al found negligible FDG uptake but intense 68 Ga-DOTATATE avidity of pulmonary metastases in a 68-year-old woman affected by primitive intracranial HPC [ 24 ].…”
Section: Evidence-based Medicine Of Pet/ct In Intracranial Solitary F...mentioning
confidence: 99%
“…Radiotherapy was performed with 59.4 Gy, which caused tumour regression and local control for several years. Eventually, the patient progressed and was evaluated for possible peptide receptor radionuclide therapy (PRRT) using [ 68 Ga]DOTATATE positron emission tomography/computed tomography (PET/CT), as previously it was described that hemangiopericytoma might show somatostatin receptor expression [ 1 ].…”
mentioning
confidence: 99%